Carbon quantum dots intercalated in polypyrrole (PPy) thin electrodes for accelerated energy storage. (20th December 2020) - Malik, Rinki; Lata, Suman; Soni, Udit; Rani, Priyanka; Malik, Rajender Singh
Highlights: Novel porous nanostructure carbon quantum dots/polypyrrole composites were successfully synthesized by direct electrochemical method. PPy/CQDs improve the electron transfer with reduction the internal resistance and charge transfer resistance. PQD 0.5 (PPy: CQDs as 95: 5 w/w) demonstrates high specific capacitance of 838 F/g at scan rate of 10 mV/s with mass loading 1.3 g/cm 2 . PQD 30 (PQD 0.5 with electro polymerization time 30 min) observed as best composite for energy storage purpose with 1073 F/g specific capacitance at a scan rate of 10 mV/s and mass loading with 1.4 g/cm 2 with cyclic stability as 62% even after 2000 cycles of charge/discharge for the electrode. Abstract: Polypyrrole (PPy) and carbon quantum dots (CQDs) based composite electrodes (PPy/CQDs or PQDs) are designed through one step electro-polymerization technique in aqueous solution for energy storage purposes. Composite electrode, thus obtained exhibits good electrochemical properties due to dotted CQDs structure comprising of high surface area with numerous active sites. Electrical conductivity of PPy was improved noticeably after modifying with CQDs. The charge transfer resistance (Rp ) diminishes from 2.7 Ω to 0.11 Ω for PQD composite due to fast charge diffusion. The impact of varied concentration of CQDs was also evaluated for optimizing the electrochemical behavior of PQDs composites and PPy: CQDs as 95: 5 w/w ratio designated as PQD 0.5 was found to be the most effective composition. Various electrochemical properties of PQDs are also correlated at different time intervals to get an effective electro-polymerized output and observed that PQD 0.5 composition processed for 30 min (PQD 30) demonstrates high specific capacitance of 1073.5 F/g at a scan rate of 10 mV/s and mass loading with 1.4 g/cm 2 of the optimized composite with a good cyclic stability as 62% even after 2000 cycles of charge/discharge for the electrode. Graphical abstract: Polypyrrole (PPy) and carbon quantum dots (CQDs) based composite electrodes (PPy/CQDs or PQDs) are designed through one step electro-polymerization technique in aqueous solution for energy storage purposes. Composite electrode, thus obtained exhibits good electrochemical properties due to dotted CQDs structure comprising of high surface area with numerous active sites. Electrical conductivity of PPy was improved noticeably after modifying with CQDs. The charge transfer resistance (Rp ) diminishes from 2.7 Ω to 0.11 Ω for PQD composite due to fast charge diffusion. The impact of varied concentration of CQDs was also evaluated for optimizing the electrochemical behavior of PQDs composites and PPy: CQDs as 95: 5 w/w ratio designated as PQD 0.5 was found to be the most fruitful composition. Various electrochemical properties of PQDs are also correlated at different time intervals to get an effective electro-polymerized output and observed that PQD 0.5 composition processed for 30 min (PQD 30) demonstrates high specific capacitance of 1073.5 F/g at a scan rate of 10 mV/s and mass loading with 1.4 g/cm 2 of the optimized composite with a valuable cyclic stability as 62% even after 2000 cycles of charge/discharge for the electrode. Image, graphical abstract